MYANMAR’S CRISIS: TERRORISM AND MIGRATION - Choudhary, Saroj (ShodhKosh: Journal of Visual and Performing Arts, 2024)
“Unjust terror leaves scars on the soul that only justice can heal.” Two major issues which Myanmar has been facing is terrorism and migration, that are not only the matter of concern of any particular place but whole country. The country is diverse where different ethnic groups and tension among them have caused violence and outrage for many years. Groups of terrorist have formed, and taking advantage of these divisions, and both the government and armed forces have played role in the violence. This thing has created fear of instability and insecurity for many lives in Myanmar. Simultaneously, the tension forced many people to leave their homes. The Rohingya crisis in particular, has gained a lot of International attention as thousands of people have been forced to leave their homes due to persecution. The huge number of refugees has created problems for neighboring countries and the International Community. This research paper looks at the root causes and solution of terrorism and migration in Myanmar, and focuses on the co-relation of these two issues. It examines how ethnic and religious tensions fuel violence, which in return forces individuals to leave their motherland. The paper will also focuses on the impact these issue lead to in the society at large. Finally, the paper discusses achievable solutions and it calls for cooperation between countries, fair policies, and a focus on both security and human rights. Myanmar’s road to peace and stability depends on addressing this issue with justice, international support, and long-term planning within the country.